2014
DOI: 10.1007/s00253-014-6078-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of antigen capture ELISA for the quantification of EIAV p26 protein

Abstract: An antigen capture enzyme-linked immunosorbent assay (AC-ELISA) was established based on two monoclonal antibodies (mAbs) for the quantification of equine infectious anemia virus (EIAV). Two p26-specific monoclonal antibodies were developed in mice. The mAb 9H8 was coated in microtiter plates as the capture antibody; the other mAb, 1G11, was coupled to horseradish peroxidase (HRP) and used as the detection antibody. The limit of detection for the EIAV p26 protein was 0.98 ng/ml, and the linearity range was 3.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Here, we focused on the immunodominant protein of PPV1, the VP2 protein, as a potential candidate for development of diagnostic and research reagents. Analysis of the PPV1 VP2 epitopes should extend our understanding of PPV1-specific immunity and accelerate the development of epitope-based diagnostic tools and synthesized peptide vaccine for PPV1 (Hu et al 2014;Kamstrup et al 1998). The report of Kamstrup et al (1998) firstly described a total of nine linear epitopes of both PPV1 VP1 and VP2 proteins and their immunogenicity was subsequently investigated.…”
Section: Mab-based Ifa To Characterize Ppv1 Replicationmentioning
confidence: 98%
See 2 more Smart Citations
“…Here, we focused on the immunodominant protein of PPV1, the VP2 protein, as a potential candidate for development of diagnostic and research reagents. Analysis of the PPV1 VP2 epitopes should extend our understanding of PPV1-specific immunity and accelerate the development of epitope-based diagnostic tools and synthesized peptide vaccine for PPV1 (Hu et al 2014;Kamstrup et al 1998). The report of Kamstrup et al (1998) firstly described a total of nine linear epitopes of both PPV1 VP1 and VP2 proteins and their immunogenicity was subsequently investigated.…”
Section: Mab-based Ifa To Characterize Ppv1 Replicationmentioning
confidence: 98%
“…The optimal conditions for the VP2 epitope-based iELISA were investigated by varying the conditions at each step (except in the colorimetric reaction and reaction termination), while maintaining the conditions at all other steps constant (Huang et al, 2011a(Huang et al, , 2011b. The mean (M) and standard deviation (SD) of the OD 405 values for 24 negative controls were used to estimate the cutoff level (Hu et al 2014;Huang et al 2011aHuang et al , 2011b. Based on this criterion, a VP2 epitope-based iELISA was established to scan 135 guinea pig sera.…”
Section: Epitope-based Ielisasmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with an immune serum obtained by immunizing rabbits with recombinant capsid protein, the assay was shown to be reasonably sensitive, with a detection limit of 0.130 ng/ml, similar to that reported for other non-commercial antigen-capture ELISAs, e.g. 0.100 ng/ml for HIV-1 capsid protein (Sanders-Beer et al, 2012), 1.25 ng/ml for the p27 antigen of avian leucosis virus (Yun et al, 2013) or 0.98 ng/ml for the p26 antigen of equine infectious anemia virus (Hu et al, 2014). The sensitivity of highly optimized commercial HIV-1 p24 ELISA kits is, of course, considerably higher.…”
Section: Discussionmentioning
confidence: 64%
“…The capsid protein (p26), which contains most antigenic epitopes for T cell-mediated immune responses, is the most abundant protein of EIAV (Alvarez et al, 2007;Hu et al, 2014). Immunohistology for p26 revealed that in addition to being detected in the alveolar walls in the lungs ( Fig.…”
Section: Eiav Dlv121 Infected a Different Panel Of Target Cells At A mentioning
confidence: 99%